Nursing care (gerontotechnologies) and ecosystemic actions for older people with HIV/AIDS (Research, Society and Development, 2021)
Objective: To know the experiences of elderly people with Human Immunodeficiency Syndrome subsidized by complexity. Method: A qualitative multiple case study, conducted in Rio Grande do Sul, Brazil, in 2015, with eight elderly people, using a form based on the International Classification of Functioning, Disability and Health. The analysis was based on three strategies Analytical: general, theoretical and descriptive. Results: Seven women and one man were interviewed; Aged between 60 and 72 years. They acquired the virus through sexual intercourse with partner / husband. They underwent diagnostic examination after routine medical consultation, presented symptom of the disease or discovered companion serology. They had difficulty accepting the serological condition, not revealing the diagnosis and presenting disappointment in the relationships and prejudice with the serological condition. Conclusion: It was verified the relevance of knowing the cases of the elderly with the Human Immunodeficiency Syndrome to elaborate actions appropriate to the needs of these elderly people.